Towards residential buildings sustainability in a religious-tourism metropolis. (April 2021) - Tayefi Nasrabadi, Mahla; Hataminejad, Hossein
Highlights: Planning for residential buildings sustainability (RBS) of Mashhad should meet the needs of two lifestyles, including pilgrims-tourists and residents. Results highlight that the physical and environmental dimensions of RBS have been taken into account less than other aspects such as socio-cultural or economic. The findings could serve as a guide for urban officials of religious-tourism metropolises (RTMs). Abstract: In light of the importance of religious-tourism metropolises (RTMs), and the lack of research about the residential buildings sustainability (RBS) of these cities, the study aims to identify the dimensions of RBS that have received less attention in previous studies and examine both the level of RBS and the correlation between less noticeable sustainable dimensions in a case of the Region-one of Mashhad RTM, as a hub of tourism and pilgrimage. Both qualitative and quantitative methods were employed to analyze the research data. The research instrument used was the structured questionnaire, using a five-point Likert scale. The data collected through the relevant documents, experts' consensus opinion, and respondents were analyzed respectively with NVivo software ver. 10, Delphi technique and SPSS software ver. 22.0. The findings of this paper highlight that despite numerous articles on the diverse aspects of RBS, the physical and environmental dimensions have been taken into account less than other aspects such as socio-cultural or economic sectors, and the studied residential buildings in physical and environmental dimensions scored at the medium and high levels of sustainability, respectively. Also, there is a strong positive linear correlation between the physical and environmental dimensions.